PURVIEW OF E-RESOURCES AND INFORMATION COMMUNICATION TECHNOLOGY IN UNIVERSITY LIBRARIES OF TAMIL NADU (International Journal of Food and Nutritional Sciences, 2022)
Libraries are called as store houses of knowledge. Sometimes back the main collection of the library is print materials. Today is the era of Information Technology, the academics would like to get updated information without spending lots of time, and hence they preferred to use the ICT based sources and services. Nowadays the library authorities fulfil the need of the academics and hence the libraries adopt to implement the ICT based sources and services.